USING SHORT STORY TO IMPROVE STUDENT’S READING COMPREHENSION (A STUDY AT THE SECOND YEAR STUDENT OF SMPN 2 KOTA BENGKULU) - Amelia Eka Frimasary; Syahrial Syahrial (JOALL (Journal of Applied Linguistics and Literature), 2017)
The objective of this research was to know the differences in students score and also to know whether the student’s interest was improved or not, after did a treatment using short story and handbook. The instrument of this research was questionnaire. The result from short story was satisfactory. The mean score from pre-test was 45.1 for experimental class and 45.25 for control class. The difference both of class was 0.15 point. The result of post-test was 55.9 for the experimental class, and 51.8 for the control class. The difference in both classes was 4.1. It can be concluded that the experiment was success. The explanation above showed that the differences in improving students’ score and interest by giving the treatment, and the differences score between two classes are significant. It means that reading activity by using short story could improve students reading comprehension in class I of SMPN 2 Kota Bengkulu.